2014
DOI: 10.1371/journal.pone.0092573
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Use of Sodium Valproate for Schizophrenia

Abstract: BackgroundOff-label use of a drug not according to its regulatory labeling has become common in medicine, especially in the field of psychiatry. Mood stabilizers are intended to be used to attenuate mood fluctuations in bipolar disorder, but their use has spread to patients with schizophrenia, as it provides greater control of impulsivity and aggressiveness. Sodium valproate is one of the most frequently used mood stabilizers in psychiatry. This study determined the prevalence of off-label use of sodium valpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
(41 reference statements)
2
20
0
Order By: Relevance
“…In our study, comparison of PANSS score between two groups ie A and B, showed that in group B (olanzapine with sodium valproate) there was a statistically significant improvement in positive symptoms (p<0.014), general psychopathology (p<0.036) and total score (p<0.018) compared to group A (olanzapine and placebo). These findings were consistent with those of Horowitz E et al 5 and Ananthavarathan 6 who showed that sodium valproate helps to reduce aggressiveness and hostility in schizophrenia. Tseng et al 7 also found effectiveness of adjunctive sodium valproate in patients of schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, comparison of PANSS score between two groups ie A and B, showed that in group B (olanzapine with sodium valproate) there was a statistically significant improvement in positive symptoms (p<0.014), general psychopathology (p<0.036) and total score (p<0.018) compared to group A (olanzapine and placebo). These findings were consistent with those of Horowitz E et al 5 and Ananthavarathan 6 who showed that sodium valproate helps to reduce aggressiveness and hostility in schizophrenia. Tseng et al 7 also found effectiveness of adjunctive sodium valproate in patients of schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…Studies found that it may help to reduce aggressiveness and hostility in schizophrenia as an "off-label" use. 5,6 Tseng et al showed significantly better treatment effect with valproate augmentation therapy in patients with schizophrenia or schizoaffective disorder. 7 Omranifard et al found that sodium valproate speeds up the recovery of positive symptoms of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…A review by Vargas-Espinosa et al mentions the use of valproate for PHN and makes a recommendation for a high-quality randomized controlled trial [29]. Studies have been conducted on valproate for indications other than epilepsy, on migraine, alcohol dependence, bipolar disorders, fibromyalgia, and schizophrenia with low evidence [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to bipolar disorder, however, robust empirical support for the efficacy of adjunctive treatment with MSMs in individuals with schizophrenia e.g., to mitigate residual psychotic symptoms, aggression, impulsivity, and mood disturbances, is lacking (Buchanan et al, 2010; Citrome 2009). Yet rates of prescribing of MSMs to individuals with schizophrenia are quite high, with an estimated 25–60% of patients receiving these agents (Citrome 2000; Citrome 2002; Horowitz et al, 2014; Olfson et al, 2009), Given the overall widespread use and the more frequent prescribing of high metabolic risk MSMs to individuals with schizophrenia, more research is needed to understand the potential harmful effects of such ‘off-label’ prescribing on the physical health of these individuals.…”
Section: Discussionmentioning
confidence: 99%